Limited Time Offer: Save 10% on all 2022 Premium Study Packages with promo code: BLOG10

# Probability Generating Functions and Moment Generating Functions

## Probability Generating Function

The probability generating function of a discrete random variable is a power series representation of the random variable’s probability density function as shown in the formula below:

\begin{align*} \text{G}\left(\text{n}\right)&=\text{P}\ \left(\text{X}\ =\ 0\right)\bullet \ \text{n}^0\ +\ \text{P}\ \left(\text{X}\ =\ 1\right)\bullet\ \text{n}^1\ +\ \text{P}\ \left(\text{X}\ =\ 2\right)\bullet\ \text{n}^2\ \\ &+\ \text{P}\ \left(\text{X}\ =\ 3\right)\bullet \ \text{n}^3\ +\ \text{P}\ \left(\text{X}=4\right)\bullet \ \text{n}^4+\cdots \\ &=\sum_{\text{i}=0}^{\infty}{\text{P}\left(\text{X}=\text{x}_\text{i}\right).\text{n}^\text{i}}=\text{E}\left(\text{n}^\text{i}\right) \end{align*}

Note: $$G\left( 1 \right) =P\left( X=0 \right) +P\left( X=1 \right) +P\left( X=2 \right) +P\left( X=3 \right) +P\left( X=4 \right) +\cdots P\left( X=r \right) =1$$

#### Example: Probability Generating Function of a Discrete Random Variable

Given the experiment of rolling a single die, find the probability generating function.

Solution

We know that:

\begin{align*} \text{G}\ \left(\text{n}\right)&=\text{E}\left(\text{n}^\text{i}\right)\\ &=0\times \text{n}^0+\left(\frac{1}{6}\right)\times\ \text{n}^1+\left(\frac{1}{6}\right)\times\ \text{n}^2+\left(\frac{1}{6}\right)\times\ \text{n}^3+\left(\frac{1}{6}\right)\times\ \text{n}^4+\left(\frac{1}{6}\right)\times\ \text{n}^5 \\ &+\left(\frac{1}{6}\right)\times\ \text{n}^6 \end{align*}

It can be useful to express $$E(X)$$ and $$Var(X)$$ as a function of the probability generating function as shown below:

\begin{align*} E\left( X \right) &=G^{ \prime }\left( 1 \right) \\ \text{Var}\left(\text{X}\right)&=\text{G}^{\prime \prime}\left(1\right)+\text{G}^{\prime}\left(1\right)-\left[\text{G}^{\prime}\left(1\right)\right]^2 \\ \end{align*}

#### Example: Probability Generating Function of a Discrete Random Variable

Given the experiment of rolling a single die, find $$E(X)$$ and $$Var(X)$$ using the probability generating function.

\begin{align*} & G\left( n \right) =0\bullet n^{ 0 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 1 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 2 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 3 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 4 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 5 }+\left( \frac { 1 }{ 6 } \right) \bullet n^{ 6 } \\ & G^{ \prime }\left( n \right) =\left( \frac { 1 }{ 6 } \right) +2\bullet \left( \frac { 1 }{ 6 } \right) \bullet n+3\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 2 }+4\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 3 }+5\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 4 }+6\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 5 } \\ & G^{ \prime }\left( 1 \right) =\left( \frac { 1 }{ 6 } \right) +2\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1+3\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 2 }+4\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 3 }+5\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 4 }+6\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 5 }=3.5 \\ & G^{ \prime \prime }\left( n \right) =2\bullet \left( \frac { 1 }{ 6 } \right) +3\bullet 2\bullet \left( \frac { 1 }{ 6 } \right) \bullet n+4\bullet 3\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 2 }+5\bullet 4\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 3 }+6\bullet 5\bullet \left( \frac { 1 }{ 6 } \right) \bullet n^{ 4 } \\ & G^{ \prime \prime }\left( 1 \right) =2\bullet \left( \frac { 1 }{ 6 } \right) +3\bullet 2\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1+4\bullet 3\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 2 }+5\bullet 4\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 3 }+6\bullet 5\bullet \left( \frac { 1 }{ 6 } \right) \bullet 1^{ 4 } = 11.667 \\ & Var\left( X \right) =G^{ ” }\left( 1 \right) +G^{ ‘ }\left( 1 \right) -\left[ G^{ ‘ }\left( 1 \right) \right] ^{ 2 }=11.667+3.5-3.5^{ 2 }=2.92 \\ \end{align*}

### Moment Generating Function

A moment generating function $$M(t)$$ of a random variable $$X$$ is defined for all real value of $$t$$ by:

$$\text{M}\left( \text{t} \right) =\text{E}\left( { \text{e} }^{ \text{tX} } \right) =\begin{cases} \sum _{ \text{x} }^{ }{ { \text{e} }^{ \text{tX} } } \text{p}\left( \text{x} \right) , \text{ if X is a discrete with mass function } \text{p}\left(\text{x}\right) \\ \int _{ -\infty }^{ \infty }{ { \text{e} }^{ \text{tX} } } \text{f}\left( \text{x} \right) \text{dx}, \text{ if X is continous with density function } \text{f}\left(\text{x}\right) \end{cases}$$

#### Example: Moment Generating Function of a Discrete Random Variable

Given the experiment of rolling a single die, find the moment generating function.

Solution

We know that:

$$M\left( t \right) =e^{ t1 }P\left( X=1 \right) +e^{ t2 }P\left( X=2 \right) +e^{ t3 }P\left( X=3 \right) +e^{ t4 }P\left( X=4 \right) +e^{ t5 }P\left( X=5 \right) +e^{ t6 }P\left( X=6 \right)$$

$$M\left( t \right) =e^{ t }\left( \frac { 1 }{ 6 } \right) +e^{ 2t }\left( \frac { 1 }{ 6 } \right) +e^{ 3t }\left( \frac { 1 }{ 6 } \right) +e^{ 4t }\left( \frac { 1 }{ 6 } \right) +e^{ 5t }\left( \frac { 1 }{ 6 } \right) +e^{ 6t }\left( \frac { 1 }{ 6 } \right)$$

As with the probability generating function, it can also be useful to use the moment generating function to calculate $$E(X)$$ and $$Var(X)$$ as shown in the formulas below:

\begin{align*} & E \left(X \right)= \mu =M^{\prime} \left(0 \right) \\ & E \left(X^2 \right)=M^{\prime\prime}\left(0 \right) \\ & Var \left(X \right)= {\sigma}^2= M^{\prime\prime} \left(0 \right)-\left[M^{‘} \left(0 \right) \right]^2 \\ \end{align*}

Consider the moment generating function above. We wish to calculate $$\text{E}\left(\text{X}\right)$$ and $$\text{Var}\left(\text{X}\right)$$.

We know that:

$$\text{E}\left(\text{X}\right)=\mu=\text{M}\prime(0)$$

The moment generating function is given by:

$$\text{M}\left(\text{t}\right)=\text{e}^\text{t}\left(\frac{1}{6}\right)+\text{e}^{2\text{t}}\left(\frac{1}{6}\right)+\text{e}^{3\text{t}}\left(\frac{1}{6}\right)+\text{e}^{4\text{t}}\left(\frac{1}{6}\right)+\text{e}^{5\text{t}}\left(\frac{1}{6}\right)+\text{e}^{6\text{t}}\left(\frac{1}{6}\right)$$

Taking the first derivative, we have:

$$\text{M}^\prime\left(\text{t}\right)=\left(\frac{1}{6}\right)\text{e}^\text{t}+\left(\frac{2}{6}\right)\text{e}^{2\text{t}}+\left(\frac{3}{6}\right)\text{e}^{3\text{t}}+\left(\frac{4}{6}\right)\text{e}^{4\text{t}}+\left(\frac{5}{6}\right)\text{e}^{5\text{t}}+\left(\frac{6}{6}\right)\text{e}^{6\text{t}}$$

Substituting $$t=0$$ in the above equation, we have:

$$\text{M}^\prime\left(0\right)=\left(\frac{1}{6}\right)+\left(\frac{2}{6}\right)+\left(\frac{3}{6}\right)+\left(\frac{4}{6}\right)+\left(\frac{5}{6}\right)+\left(\frac{6}{6}\right)=3.5$$

For the variance, we know that:

$$\text{Var}\left(\text{X}\right)=\sigma^2=\text{E}\left(\text{X}^2\right)-\left[\text{E}\left(\text{X}\right)\right]^2=\text{M}^{\prime\prime}\left(0\right)-\left[\text{M}^\prime\left(0\right)\right]^2$$

Now taking the second derivative of the moment generating function, we have:

\begin{align*} \text{M}^{\prime \prime}\left(\text{t}\right)&=\left(\frac{1}{6}\right)\text{e}^\text{t}+\left(\frac{4}{6}\right)\text{e}^{2\text{t}}+\left(\frac{9}{6}\right)\text{e}^{3\text{t}}+\left(\frac{16}{6}\right)\text{e}^{4\text{t}}+\left(\frac{25}{6}\right)\text{e}^{5\text{t}}+\left(\frac{36}{6}\right)\text{e}^{6\text{t}} \\ \Rightarrow\ \text{M}^\prime\left(0\right)&=\left(\frac{1}{6}\right)+\left(\frac{4}{6}\right)+\left(\frac{9}{6}\right)+\left(\frac{16}{6}\right)+\left(\frac{25}{6}\right)+\left(\frac{36}{6}\right)=15.167 \\ \text{Var}\left(\text{X}\right)&=\sigma^2=\text{M}^{\prime\prime}\left(0\right)-\left[\text{M}^\prime\left(0\right)\right]^2=15.167-{3.5}^2=2.92 \end{align*}

#### Example: Moment Generating Function of Discrete Random Variables

Suppose that the discrete random variable $$X$$ has a distribution:

$$\text{f}\left(\text{x}\right)= \begin{cases} \frac { 1 }{ 2 } ,\text{x}=1 \\ \frac { 3 }{ 8 } ,\text{x}=2 \\ \frac { 1 }{ 8 } ,\text{x}=3 \end{cases}$$

a. Find the moment generating function $$M(t)$$.

Solution

We know that:\begin{align*} \text{M}\left(\text{t}\right)&=\text{E}\left(\text{e}^{\text{xt}}\right)=\left(\text{x}+\text{a}\right)^\text{n}=\sum_{\text{x}}{\text{e}^{\text{xt}}\text{f}(\text{x})}\ \\ &=\text{e}^\text{tf}\left(1\right)+\text{e}^{2\text{t}}\text{f}\left(2\right)+\text{e}^{3\text{t}}\text{f}\left(3\right) \\ &=\left(\frac{1}{2}\right)\text{e}^{\prime \text{t}}+\left(\frac{3}{8}\right)\text{e}^{2\text{t}}+\left(\frac{1}{8}\right)\text{e}^{3t} \\ &\therefore\ \text{M}\left(\text{t}\right)=\frac{1}{2}\text{e}^\text{t}+\frac{3}{8}\text{e}^{2\text{t}}+\frac{1}{8}\text{e}^{3\text{t}} \end{align*}

b. Use the moment generating function to find the mean of X.

Solution

The mean of X is $$\text{E}\left(\text{X}\right)=\text{M}\prime(0)$$.We are given that:\begin{align*} \text{M}\left(\text{t}\right)&=\frac{1}{2}\text{e}^\text{t}+\frac{3}{8}\text{e}^{2\text{t}}+\frac{1}{8}\text{e}^{3t} \\ &{\Rightarrow \text{M}}^\prime(\text{t})=\frac{1}{2}\text{e}^t+\frac{2\times3}{8}\text{e}^{2\text{t}}+\frac{3\times1}{8}\text{e}^{3t} \\ &=\frac{1}{2}\text{e}^t+\frac{6}{8}\text{e}^{2\text{t}}+\frac{3}{8}\text{e}^{3\text{t}} \\ \text{M}^\prime\left(0\right)&=\frac{1}{2}\text{e}^0+\frac{6}{8}\text{e}^{2\times0}+\frac{3}{8}\text{e}^{3\times0}=\frac{1}{2}+\frac{6}{8}+\frac{3}{8}=\frac{13}{8} \end{align*}Mean of $$\text{X}= \text{M’} (0) = \frac{13}{8}$$

c. Use the moment generating function to find the variance of X.

Solution

We know that:$$\text{Var}\ \left(\text{X}\right) \text{E}\left(\text{X}^2\right)-\text{E}\left(\text{X}\right)^2=\text{M}^{\prime\prime}\left(0\right)-{[\text{M}}^{\prime}\left(0\right)]2$$From (b), we have:\begin{align*} \text{M}^{\prime}(\text{t})&=\frac{1}{2}e^t+\frac{6}{8}\text{e}^{2\text{t}}+\frac{3}{8}\text{e}^{3\text{t}} \\ {\Rightarrow \text{M}}^{\prime\prime}\left(\text{t}\right)&=\frac{1}{2}\text{e}^\text{t}+\frac{2\times6}{8}\text{e}^{2\text{t}}+\frac{3\times3}{8}\text{e}^{3\text{t}}=\frac{1}{2}\text{e}^\text{t}+\frac{12}{8}\text{e}^{2\text{t}}+\frac{9}{8}\text{e}^{3\text{t}} \\ &{\therefore \text{M}}^{\prime\prime}\left(0\right)=\frac{1}{2}\text{e}^0+\frac{12}{8}\text{e}^{2\times0}+\frac{9}{8}\text{e}^{3\times0} \\ &=\frac{1}{2}+\frac{12}{8}+\frac{9}{8}=\frac{25}{8} \\ \text{Var}\ (\text{X})&=\text{M}^{\prime\prime}\left(0\right)-\text{M}^{\prime}(0)² \\ &=\frac{25}{8}-\left(\frac{13}{8}\right)^2=\frac{25}{8}-\frac{169}{64}=\frac{31}{64} \end{align*}

#### Example: Moment Generating Function of a Continuous Distribution

Given the following probability density function of a continuous random variable:

$$f\left( x \right) =\begin{cases} 0.2{ e }^{ -0.2x }, & 0\le x\le \infty \\ 0, & otherwise \end{cases}$$

Find the moment generating function.

Solution

For a continuous distribution,

$$\text{M}\left(t\right)=\ \int_{-\infty}^{\infty}{\text{e}^{\text{tx}}\text{f}\left(\text{x}\right)\text{dx}}$$

So, in this case:

\begin{align*} \text{M}\left(\text{t}\right)&=\int_{0}^{\infty}{\text{e}^{\text{tx}}\times\left(0.2\text{e}^{-0.2\text{x}}\right)\times \text{dx}} \\ \text{M}\left(\text{t}\right)&=\int_{0}^{\infty}{0.2\text{e}^{\text{x}\left(\text{t}-0.2\right)}\text{dx}=\left[\frac{0.2\text{e}^{\text{x}\left(t-0.2\right)}}{\text{t}-0.2}\right]_{\text{x}=0}^{\text{x}=\infty}=-\frac{0.2}{t-0.2}} \end{align*}

As with the moment generating function of the discrete distribution, we can use the moment generating function of a continuous distribution to calculate $$E(X)$$ and $$Var(X)$$ using the formulae below:

\begin{align*} E \left(X \right) & = \mu=M^{\prime}\left(0 \right) \\ E \left(X^2 \right) & =M^{\prime\prime} \left(0 \right) \\ Var \left(X \right) & = {\sigma}^2= M^{\prime\prime} \left(0 \right)-\left[M^{\prime} \left(0\right) \right]^2 \\ \end{align*}

#### Example: Calculating Expectation and Variance for MGF

Given the moment generating function shown below, calculate $$E(X)$$ and $$Var(X)$$.

$$\text{M}\left(\text{t}\right)=\frac{0.2}{\text{t}-0.2\ }$$

Solution

Note that we can write:

$$\text{M}\left(\text{t}\right)=\frac{0.2}{t-0.2\ }=-0.2\left(\text{t}-0.2\right)^{-1}$$

So that:

$$\text{M}^\prime\left(\text{t}\right)=0.2\left(\text{t}-0.2\right)^{-2}$$

We know that:

$$\text{E}\left(\text{X}\right)=\text{M}^\prime\left(0\right)=0.2\left(-0.2\right)^2=\frac{1}{0.2}=5$$

Also,

\begin{align*} {\text{E}\left(\text{X}^2\right)}&=\text{M}^{\prime\prime} \left(\text{t}\right)=-2\times0.2\left(\text{t}-0.2\right)^{-3}=-0.4\left(\text{t}-0.2\right)^{-3} \\ \Rightarrow \text{M}^{\prime\prime}\left(0\right)&=-0.4\left(-0.2\right)^{-3}=50 \\ \therefore \text{Var}\left(\text{X}\right)&=\sigma^2=\text{M}^{\prime\prime}\left(0\right)-\left[\text{M}^\prime\left(0\right)\right]^2=50-5^2=25 \end{align*}

## Moment Generating Functions of Common Distributions

### Binomial Distribution

The moment generating function for $$X$$ with a binomial distribution is an alternate way of determining the mean and variance.

Let us perform n independent Bernoulli trials, each of which has a probability of success $$p$$ and probability of failure $$1-p$$. Thus, the probability mass function (PMF) is:

$$\text{f}\left(\text{x}\right)=\binom{\text{n}}{\text{x}}\text{p}^\text{x}\left(1-\text{p}\right)^{\text{n}-\text{x}}$$

Where, $$\binom{\text{n}}{\text{x}}$$ can be written as $$\text{C}(\text{n},\text{x})$$ and denotes the number of combinations of n elements taken $$x$$ at a time; where $$x$$ can take on values $$0,1,2,3, …,n$$.

Using the PMF, we can obtain the moment generating function of $$X$$:

$$\text{M}\left(\text{t}\right)=\sum_{\text{x}=0}^{\text{n}}{\text{e}^{\text{tx}}\binom{\text{n}}{\text{x}}\text{p}^\text{x}\left(1-\text{p}\right)^{\text{n}-\text{x}}}$$

Combine the terms with exponential of $$x$$:

$$\text{M}\left(\text{t}\right)=\sum_{\text{x}=0}^{\text{n}}{\left(\text{pe}^\text{t}\right)^\text{x}\binom{\text{n}}{\text{x}}\ \left(1-\text{p}\right)^{\text{n}-\text{x}}}$$

By using the binomial formula, the expression above is simply:

$$M \left(t \right)={\left(p{e}^{t}+1-p \right)}^n$$

#### Mean and Variance

In order to calculate the mean and variance, we need to find both $$\text{M}\prime(0)$$ and $$\text{M}\prime\prime(0)$$.

First, you start by calculating the derivatives, then evaluate each of them at $$t=0$$. The 1st derivative of the moment generating function is:

$$\text{M}^\prime\left(\text{t}\right)=\text{n}\left(\text{pe}^\text{t}+1-\text{p}\right)^{\text{n}-1}\text{pe}^\text{t} \\ \Rightarrow \text{M}^\prime\left(0\right)=\text{n}\left(\text{p}+1-\text{p}\right)^{\text{n}-1}\text{p}=\text{np}$$

If we differentiate the second time, we get:

$$\text{M}^{\prime\prime}\left(\text{t}\right)=\text{n}\left(\text{n}-1\right)\left(\text{pe}^t+1-\text{p}\right)^{\text{n}-2}\left(\text{pe}^\text{t}\right)^2+\text{n}\left(\text{pe}^\text{t}+1-\text{p}\right)^{\text{n}-1}\text{pe}^\text{t}$$

So that:

$$\text{E}\left(\text{X}^2\right)=\text{M}^{\prime\prime}\left(0\right)=\text{n}\left(\text{n}-1\right)\text{p}^2+\text{np}$$

We know that:

$$\text{Var}\left(\text{X}\right)=\text{E}\left(\text{X}^2\right)-\left[\text{E}\left(\text{X}\right)\right]^2=\text{n}\left(\text{n}-1\right)\text{p}^2+\text{np}-\text{n}^2\text{p}^2=\text{np}(1-\text{p})$$

### Negative Binomial Distribution

The moment generating function of a negative binomial distribution is given by:

$$M\left( t \right) ={ \left[ \frac { p{ e }^{ t } }{ 1-\left( 1-p \right) { e }^{ t } } \right] }^{ r }$$

Which is derived as follows:

\begin{align*} \text{M}\left(\text{t}\right)=\text{E}\left[\text{e}^{\text{tX}}\right]&=\sum_{\text{k}=\text{r}}^{\infty}{\text{e}^{\text{tk}}\binom{\text{k}-1}{\text{r}-1}\left(1-\text{p}\right)^{\text{k}-\text{r}}\text{p}^\text{r}} \\ &=\sum_{\text{k}=\text{r}}^{\infty}{\text{e}^{\text{tk}}\binom{\text{k}-1}{\text{r}-1}\left(1-\text{p}\right)^{\text{k}-\text{r}}\text{p}^\text{r}\times\frac{\text{e}^{\text{tr}}}{\text{e}^{\text{tr}}}} \\ &=\sum_{\text{k}=\text{r}}^{\infty}{\text{e}^{\text{t}\left(\text{k}-\text{r}\right)}\binom{\text{k}-1}{\text{r}-1}\left(1-\text{p}\right)^{\text{k}-\text{r}}{(\text{e}}^\text{t}{\text{p})}^\text{r}} \\ &=\left(\text{e}^\text{t} \text{p}\right)^\text{r}\sum_{\text{k}=\text{r}}^{\infty}{\binom{\text{k}-1}{\text{r}-1}{(\text{e}}^\text{t}{\left(1-\text{p}\right))}^{\text{k}-\text{r}}} \\ \end{align*}

Setting $$j=k-r$$,

$$\text{M}\left(\text{t}\right)={\text{e}^\text{t}}{\text{p}}^\text{r}\sum_{\text{j}=0}^{\infty}{{\text{j}+\text{r}-1}{\text{r}-1}(\text{e}^\text{t}{\left(1-\text{p}\right))}^\text{j}} \\ \frac{\text{e}^\text{t}{\text{p})}^\text{r}}{(1-\text{e}^\text{t}(1-{\text{p}))}^\text{r}}=\text{M}\left(\text{t}\right)=\left[\frac{\text{pe}^\text{t}}{1-\left(1-\text{p}\right)\text{e}^\text{t}}\right]^\text{r}$$

### Geometric Distribution

The moment generating function of geometric distribution is given by:

$$M\left( t \right) =\frac { p{ e }^{ t } }{ 1-\left( 1-p \right) { e }^{ t } }$$

The moment generating function for $$\text{X}\sim geometric \left(\text{p}\right)$$ is derived as:

\begin{align*} \text{M}\left(\text{t}\right)&=\text{E}[\text{e}^{\text{tX}}] \\ &=\sum_{\text{x}=0}^{\infty}{\text{e}^{\text{tx}}\text{p}\left(1-\text{p}\right)^\text{x}} \\ \text{Step}\ (\text{i})&=\text{p}\sum_{\text{x}=0}^{\infty}{(\text{e}^\text{t}{\left(1-\text{p}\right))}^\text{x}} \end{align*}

Where the series in step (i) converges only if:

$$\left(1-\text{p}\right)\text{e}^\text{t}$$

Meaning, only if:

$$\text{e}^\text{t}<\frac{1}{(1-\text{p})}$$

The condition becomes $$\text{t}<-\ln(1-\text{p})$$ by taking the natural log of both sides.

$$\text{M}(\text{t})=\frac{\text{p}}{1-\left(1-\text{p}\right)\text{e}^\text{t}}$$

### Poisson Distribution

Let $$X$$ be a discrete random variable with a Poisson distribution with parameter $$\lambda$$ for some $$\lambda\epsilon\text{R}>0$$.

Then the moment generating function $${\text{M} }_{\text{X}}$$ of X is given by:

$$\text{M}\left(\text{t}\right)=\text{e}^{\lambda\left(\text{e}^\text{t}-1\right)}$$

#### Proof

From Poisson distribution definition, $$X$$ has a PMF:

$$\text{P}\left(\text{X}=\text{n}\right)=\frac{\lambda^\text{n} \text{e}^{-\lambda}}{\text{n}!}$$

From the moment generating function definition:

$$\text{M}_\text{X}\left(\text{t}\right)=\text{E}\left(\text{e}^{\text{tX}}\right)=\sum_{\text{n}=0}^{\infty}{\text{P}\left(\text{X}=\text{n}\right)\text{e}^{\text{tn}}}$$

Thus,

$$\text{M}_\text{X}\left(\text{t}\right)=\sum_{\text{n}=0}^{\infty}\frac{\lambda^\text{n} \text{e}^{-\lambda}}{\text{n}!}\text{e}^{\text{tn}}\\ =\text{e}^ {-\lambda}\sum_{\text{n}=0}^{\infty}\frac{\left(\lambda \text{e}^\text{t}\right)^\text{n}}{\text{n}!}$$

By the power series expansion for the exponential function:

$$=\text{e}^{-\lambda}\sum_{\text{n}=0}^{\infty}\frac{\left(\lambda \text{e}^\text{t}\right)^\text{n}}{\text{n}!}{=\text{e}}^{-\lambda}\text{e}^{\lambda \text{e}^\text{t}\ \ \ \ \ }\ \ =\text{e}^{\lambda\left(\text{e}^\text{t}-1\right)}$$

### Uniform Distribution

Let $$\text{X}~\text{U}[\text{a}\ .\ .\text{b}]$$ for some $$\text{a},\ \text{b}\ \epsilon\mathbb{\text{R}},\ \text{a}\neq\ \text{b},$$ where U is the continuous uniform distribution

Then the moment generating function of $$X$$, $${\text{M}}_{\text{X}}$$, is given by:

$${\text{M}}_{\text{X}}\left(\text{t}\right) = \begin{cases} \frac { \text{e}^{ \text{tb} }-\text{e}^{ \text{ta} } }{ \text{t}(\text{b}-\text{a}) } & \text{t}\neq 0 \\ 1 & \text{t}= 0 \\ \end{cases}$$

#### Proof

The definition of continuous uniform distribution, $$X$$ has a PMF of:

$$\text f_{\text X}\left(\text x\right)= \begin{cases} \frac { 1 }{ \text{b}-\text{a} } & \text{a}\le \text{x}\le \text{b} \\ 0 & \text{otherwise} \\ \end{cases}$$

The moment generating function definition goes as follows:

$$\text{M}_\text{X}\left(t\right)=\mathbb{\text{E}}\left[\text{e}^{\text{tX}}\right]=\int_{\infty}^{\infty}{\text{e}^{\text{tx}}\text{f}_\text{X}(\text{x})\text{dx}}$$

Then, we first have to consider that $$\text{t}\neq 0$$.

Thus,

\begin{align*} \text{M}_\text{X}\left(\text{t}\right)&=\int_{\infty}^{\text{a}}{0\text{e}^{\text{tx}}\text{dx}+\int_{\text{a}}^{\text{b}}{\frac{\text{e}^{\text{tx}}}{\text{b}-\text{a}}\text{dx}+\int_{\text{b}}^{\infty}{0\text{e}^{\text{tx}}\text{dx}}}} \\ &{=\left[\frac{\text{e}^{\text{tx}}}{\text{t}\left(\text{b}-\text{a}\right)}\right]}_\text{a}^\text{b}\ \text{ by primitive of e}^{\text{ax}}\ (\text{a fundamental theorem of calculus}) \\ \text{M}_\text{X}(\text{t})&=\frac{\text{e}^{\text{tb}}-\text{e}^{\text{ta}}}{\text{t}(\text{b}-\text{a})} \end{align*}

Note: For $$t=0$$, we have $$\mathbb{\text{E}}\left[\text{X}^0\right]=\mathbb{\text{E}}\left[1\right]=1$$.

### Exponential Distribution

If $$X$$ has an exponential distribution, then the formulae below apply:

$$\text{M}\left(\text{t}\right)=\frac{\lambda}{\lambda-\text{t}}$$

#### Proof

\begin{align*} \text{M}\left(\text{t}\right)&=\text{E}\left(\text{e}^{\text{tX}}\right)\\ &=\int_{0}^{\infty}{\text{e}^{\text{tx}}\lambda \text{e}^{-\lambda \text{x}}\text{dx}} \\ &=\lambda\int_{0}^{\infty}{\text{e}^{-\left(\lambda-t\right)\text{x}}\ \text{dx}\ }\\ &=\frac{\lambda}{\lambda-\text{t}}\ for\ \text{t}<\lambda \end{align*}

Note that:

\begin{align*} \text{M}^\prime\left(\text{t}\right)& =\frac{\lambda}{\left(\lambda-\text{t}\right)^2} \\ \Rightarrow \text{M}^\prime\left(0\right) & =\frac{1}{\lambda} \\ \therefore \text{E}\left(\text{X}\right) & =\frac{1}{\lambda} \end{align*}

Also,

\begin{align*} \text{M}^{\prime\prime}\left(\text{t}\right)&=\frac{2\lambda}{\left(\lambda-t\right)^3}\\ \Rightarrow\ \text{M}^{\prime\prime}\left(0\right) & =\frac{2}{\lambda^2} \\ \therefore\ \text{Var}\left(\text{X}\right)& =\frac{2}{\lambda^2}-\left(\frac{1}{\lambda}\right)^2=\frac{1}{\lambda^2} \end{align*}

### Gamma Distribution

If $$X$$ has a gamma distribution over the interval $$[0,\ \infty]$$ with parameters $$k$$ and $${ \lambda }$$, then the formulae below apply:

$$\text{M}\left(\text{t}\right)=\left[\frac{\lambda}{\lambda-\text{t}}\right]^\text{s}$$

### Normal Distribution

Let $$\text{x}\sim \text{N}(\mu,\ \sigma^2)$$, then the moment generating function is:

$$\text{M}\left(\text{t}\right)=\text{e}^{\mu \text{t}+\frac{\left(\sigma^2\text{t}^2\right)}{2}}$$

Intuitively, the MGF of a standard normal variable is:

$$\text{M}\left(\text{t}\right)=\text{e}^\frac{\text{t}^2}{2}$$

Learning Outcome

Topic 2.e: Univariate Random Variables – Define probability generating functions and moment generating functions and use them to calculate probabilities and moments.

Shop CFA® Exam Prep

Offered by AnalystPrep

Featured Shop FRM® Exam Prep Learn with Us

Subscribe to our newsletter and keep up with the latest and greatest tips for success
Shop Actuarial Exams Prep Shop GMAT® Exam Prep

Daniel Glyn
2021-03-24
I have finished my FRM1 thanks to AnalystPrep. And now using AnalystPrep for my FRM2 preparation. Professor Forjan is brilliant. He gives such good explanations and analogies. And more than anything makes learning fun. A big thank you to Analystprep and Professor Forjan. 5 stars all the way!
michael walshe
2021-03-18
Professor James' videos are excellent for understanding the underlying theories behind financial engineering / financial analysis. The AnalystPrep videos were better than any of the others that I searched through on YouTube for providing a clear explanation of some concepts, such as Portfolio theory, CAPM, and Arbitrage Pricing theory. Watching these cleared up many of the unclarities I had in my head. Highly recommended.
Nyka Smith
2021-02-18
Every concept is very well explained by Nilay Arun. kudos to you man!